Alcohol-based Hand Rubs Are Effective for Reduction of Multi-Drug Resistant Candida. (4th October 2017) - Edmonds-Wilson, Sarah; Yeik, Alyssa
Abstract: Background: Hand hygiene is one of the most important measures for preventing the spread of infection. However as new, multi-drug resistant organisms emerge there is the question as to whether marketed products are effective against them. Multi-drug resistant Candida auris (MDRCA) was first reported as an infectious agent in humans in 2009 and has since been implicated in a growing number of infections. In June 2016 the US CDC issued a clinical alert to healthcare facilities warning of the potential for MDRCA transmission and infection within healthcare facilities and the importance of infection control measures. To date, data on the effectiveness alcohol-based hand rubs (ABHRs) against MDRCA has been lacking. The objective of the study was to test the fungicidal efficacy of three commercial ABHRs against MDRCA. Methods: Three test products, two ABHR foams and one gel, each containing 70% ethanol, were evaluated for fungicidal activity against MDRCA (AR-Bank #0390) using an in vitro time kill method (ASTM E2783-11). Reductions of the microorganism were determined following exposure to test products for 15 and 30 seconds. Results: Each of the three ABHR achieved complete reduction, 6.7889 log10 (≥99.9999%) of MDRCA at the 15 and 30 seconds exposure times. Conclusion: Health care workers should continue to use ABHRs as indicated for preventing the transmission of infection. This data indicates these products effectively kill MDRCA, and further highlights the importance of compliance with hand hygiene guidelines in healthcare settings. Disclosures: S. Edmonds-Wilson, GOJO Industries: Employee, Salary